COMPARATIVE ANALYSIS OF FEMININE TERMS IN UZBEK AND ENGLISH LITERATURE - Milikova Maftuna Akmaljanovna; Rustamova Adash Eshankulovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This article conducts a rigorous comparative analysis of feminine terms in Uzbek and English literature, exploring the intricate interplay between language, culture, and gender. Employing a multidisciplinary approach, the study investigates how linguistic expressions of femininity in both languages are shaped by historical, societal, and cultural factors. By examining the semantic nuances of feminine terms, the research aims to unravel the complex layers of gender representation in literature.